Topological study of diverse hydrogen‐bonded patterns found in a system of a nickel(II) complex and the sulfate anion. Issue 3 (23rd February 2018) - Harvey, Miguel Angel; Suarez, Sebastián; Zolotarev, Pavel N.; Proserpio, Davide M.; Baggio, Ricardo
Abstract : Bis[2, 6‐bis(1 H ‐benzimidazol‐2‐yl)pyridine]nickel(II) units combine via sulfate bridges to produce porous solids, connected via strong charge‐assisted hydrogen bonds. The frameworks are analyzed using crystallographic and topological approaches. Abstract : A nickel(II) coordination complex, bis[2, 6‐bis(1 H ‐benzimidazol‐2‐yl‐κ N 3 )pyridine‐κ N ]nickel(II) sulfate, [Ni(C19 H13 N5 )2 ]SO4 or [Ni(H2 L )2 ]SO4, having four peripheral tetrahedrally oriented N—H donor units, combines with sulfate bridges to create hydrogen‐bonded structures of varied dimensionality. The three crystal structures reported herein in the space groups P 21 21 21, I and Pccn are defined solely by strong charge‐assisted N—H…O hydrogen bonds and contain disordered guests (water and dimethylformamide) that vary in size, shape and degree of hydrophilicity. Two of the compounds are channelled solids with three‐dimensional structures, while the third is one‐dimensional in nature. In spite of their differences, all three present a striking resemblance to the previously reported anhydrous relative [Guo et al. (2011). Chin. J. Inorg. Chem. 27, 1517–1520], which is considered as the reference framework from which all three title compounds are derived. The hydrogen‐bonded frameworks are described and compared using crystallographic and topological approaches.